2022
DOI: 10.1007/s43630-022-00195-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epigenetic regulation of seasonal reproduction in Terai tree frog (Polypedates teraiensis)

Abstract: Seasonal breeders predominantly use photoperiod as the predictable environmental cue to time their reproduction. Terai tree frogs are long-day seasonal breeders, but the molecular mechanism is unknown. We tested the role of different photoperiodic conditions on expression levels of candidate genes involved in seasonal reproduction and epigenetic regulation. Four experiments were performed. In experiment 1, frogs were exposed to long (LD: 16L:8D) or short photoperiod (SD: 8L:16D). In experiment 2, animals were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Concurrent with the increase in DIO2 expression, there is a decrease in type 3 deiodinase (DIO3) expression. This reciprocal switch in hypothalamic deiodinase expression between long and short photoperiods has been confirmed in a number of seasonal breeders (Borah et al, 2022;Nakao et al, 2008;Pérez et al, 2021;Stevenson & Ball, 2012;Wang et al, 2019;Yasuo et al, 2005). Deiodinase enzymes are key regulators of thyroid hormones with DIO3 acting to inactivate both bioactive triiodothyronine (T3) and thyroxine (T4), while DIO2 serves as an activating enzyme converting T4, abundant in circulation but low bioactivity, into bioactive T3.…”
Section: Canonical Model Of Long Day Seasonal Breeding In Birdsmentioning
confidence: 85%
“…Concurrent with the increase in DIO2 expression, there is a decrease in type 3 deiodinase (DIO3) expression. This reciprocal switch in hypothalamic deiodinase expression between long and short photoperiods has been confirmed in a number of seasonal breeders (Borah et al, 2022;Nakao et al, 2008;Pérez et al, 2021;Stevenson & Ball, 2012;Wang et al, 2019;Yasuo et al, 2005). Deiodinase enzymes are key regulators of thyroid hormones with DIO3 acting to inactivate both bioactive triiodothyronine (T3) and thyroxine (T4), while DIO2 serves as an activating enzyme converting T4, abundant in circulation but low bioactivity, into bioactive T3.…”
Section: Canonical Model Of Long Day Seasonal Breeding In Birdsmentioning
confidence: 85%
“…Recent studies have revealed the role of epigenetics in regulating the expression of seasonal reproductive key genes [10][11][12][13][14][15]. For example, it was reported that a short photoperiod inhibited hypothalamic DNA methyltransferase expression and reduced dio3 promoter DNA methylation, which up-regulated dio3 expression and induced gonadal regression [13].…”
Section: Introductionmentioning
confidence: 99%